Inclusão da fibra do resíduo peletizado de culturas de cana de açúcar em dietas de milho grão inteiro para bovinos. - Vieira, Elis-Regina de Queiroz (Universidade Federal do Tocantins, 2023)
This report Supervised was conducted at the Centre for Enterprise Search Agrocriam Animal Nutrition and Seed Ranch is located in San Francisco in Goiânia- GO in the period 21/12/2013 to 21/10/2013, will during the internship was analyzed the inclusion of increasing amounts of pelleted residue of sugarcane crops in diets of corn grain on metabolism and performance of cattle in feedlots . Feeding steers , analysis score troughs , collect and weigh the leftovers , monitoring of health management , Feeding behavior , content analysis of rumen fluid to measure the concentration of ammonia nitrogen ( NH3-N ) : During this period activities were performed as , analysis of ruminal fluid viscosity , pH , short-chain fatty ( SCFA ) and protozoa in rumen fluid acids , and monitoring of supply of titanium ( 10 g / animal / day) directly into the rumen of steers dioxide to estimate fecal excretion , animal weighing and tabulating data. Through the internship the company Agrocria gave me , I had the opportunity to interact with their team, which provided a rich exchange of information . From the theoretical knowledge acquired at the university was able to establish a relationship with the activities implemented during the internship.